The selection of suitable sites for traditional charcoal production: ideas and practice in southern Switzerland. (July 2017) - Krebs, Patrik; Pezzatti, Gianni Boris; Stocker, Markus; Bürgi, Matthias; Conedera, Marco
Abstract: In the valleys of the southernmost canton of Switzerland there are numerous charcoal production sites (CPS) where, in the past, charcoal burners produced wood charcoal which was mainly exported to the urban centres of Lombardy. Through a complete field survey in three study areas totaling 16.4 km 2, 1070 sites were mapped, inventoried and their position analyzed with respect to land surface curvature. Generally, wood carbonization was carried out far from the top of ridges, suggesting a preference for concave sites. In this paper we investigate the reasons behind this distribution pattern. Scientific literature and ethnographic accounts were reviewed to find site characteristics that charcoal burners took into consideration. We then analysed the correspondence between these written sources and evidence of charcoal production sites through a spatial analysis and an experimental approach focusing on the inventoried sites. In particular, we used a new GIS tool to extract elevation profiles from a high-resolution elevation model to calculate the impact of terrain curvature on wood transport. In agreement with the contemporary literature, we explain the higher density of CPS in proximity to the bottom of runoff channels in terms of ease of transport of wood, water availability, wind protection and soil thickness. Observed differences among the study areas may be partially explained by the inverse relationship between the density of carbonization platforms along runoff channels and the average slope of the channels. Finally, by taking into account the distribution of CPS in other regions of the world, we summarize the influence of environmental factors on the relationship between CPS and the stream network. Highlights: Reviews literature on site conditions for traditional charcoal production. Maps 1070 charcoal production sites (CPS) in southern Switzerland. Examines CPS position in terms of energy consumption for wood transport. Discusses the importance of water availability, wind protection and soil thickness. Shows that density of CPS along runoff channels is related to the slope of the channels.